2017
DOI: 10.1103/physrevb.96.014436
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of nonergodic ferromagnetic/antiferromagnetic ordering and magnetocalorics in antiperovskite Mn3SnC

Abstract: We investigated the time dependence of the magnetic configuration at the mixed magnetic magnetostructural transition in Mn 3 SnC. The nonergodic nature of the transition involves the stabilization of a final magnetic configuration that involves additional AF ordering which is not present when the transition is initiated and develops only in time. We show the presence of the nonergodicity over a time scale of about 1 hour by field and time-dependent magnetization studies. Two characteristic times related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 20 publications
3
8
1
Order By: Relevance
“…A magnetic phase transition from PM state to FIM state takes place at ≈279 K for both IP and OOP fields during the cooling process. This transition temperature is slightly higher than that of the powder results [ 27 ] (275 K) and lower than the result of the literature [ 28 ] (293 K). The magnetization of OOP was close to that of IP at 10 000 Oe, but it was surprisingly smaller than that of IP magnetization by a factor of 3 under 100 Oe (In other words, the OOP magnetizations show larger splitting than IP magnetizations).…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…A magnetic phase transition from PM state to FIM state takes place at ≈279 K for both IP and OOP fields during the cooling process. This transition temperature is slightly higher than that of the powder results [ 27 ] (275 K) and lower than the result of the literature [ 28 ] (293 K). The magnetization of OOP was close to that of IP at 10 000 Oe, but it was surprisingly smaller than that of IP magnetization by a factor of 3 under 100 Oe (In other words, the OOP magnetizations show larger splitting than IP magnetizations).…”
Section: Resultscontrasting
confidence: 72%
“…Possibly, the FM-ordered Mn atoms along the IP axis and a large amount of AFM-ordered Mn atoms are arranged along the other planes. [28][29][30][31][32] The AFM magnetic moment is larger than the FM magnetic moment and it transforms to the FM phase with increasing external magnetic field. Hence, the IP net magnetization is much larger that OOP net magnetization under low magnetic field, and magnetization tends to equilibrium under high magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…While the longer Mn-Mn bond distances aid the ferromagnetic transition (T C = 242 K) from a room temperature paramagnetic (PM) state in Mn 3 GaC, an abrupt decrease in the shorter Mn-Mn distances at T ms = 178 K explains the first order magnetostructural transition to the AFM ground state described by 20,22]. On the other hand Mn 3 SnC, though it exhibits a single volume discontinuous transition from the PM state to a state with complex magnetic order at about T ms ∼ 279 K, time dependent magnetization measurements at the first order transition temperature illustrate an early development of FM order on all three Mn spins along the 001 direction followed by a flipping of spins of two of the Mn atoms to give an additional AFM order at a later time [23]. Local structure reports have demonstrated that the Mn 6 C octahedron in Mn 3 SnC elongates along one direction and shrinks along the other two while preserving the overall cubic symmetry of the unit cell.…”
Section: Introductionmentioning
confidence: 97%
“…Magnetic spin glass (SG) materials exhibit unusual ground states and represent ideal examples of glassy systems. This makes them an attractive model system for the study of glassiness in fields including physics, economics, biology, and climate sciences. In a magnetically glassy system, networks of competing effects, such as simultaneous ferromagnetic and antiferromagnetic coupling modes, can lead to multiple “quenched” states which are stable but not necessarily ground states. , A hallmark of SGs is nonergodic behavior, where separate states are stable without accessible interconversion, even if they are degenerate. Such SG behavior is believed to be critical to many magnetoresistive and exchange bias mechanisms that are desired for a variety of applications including next generation magnetic data storage and quantum information sciences. In these applications, the ability to programmably switch between different spin states beyond simple ferromagnetic memory is highly desirable.…”
Section: Introductionmentioning
confidence: 99%